Methodological and practical approaches and principles of implementation of vim technologies in the activities of construction participants - Vakhovych, I.V.; Demianenko, O. O.; Dubinin, D.V. (Ways to Improve Construction Efficiency, 2023)
In an era marked by constant technological changes and the transition of many business processes of enterprises to digital reality, construction participants are forced to review their principles and methods of construction work in order to remain at the forefront of innovative activities. This article examines methodological and practical approaches, as well as the main principles used for the successful integration of ideology, technologies and principles of building information modeling (BIM) into the operational structure of construction participants and stakeholders (using the example of engineering enterprises).The methodology lays the foundation for the implementation of BIM, emphasizing the strategic and combination of systemic, situational, function-oriented and process-oriented approaches, provides guidance to companies on adapting the implementation of building information modeling to improve productivity, optimize work processes and optimize overall project results. As a result of the transformative impact of BIM on project stages, from initial planning and design to modeling, construction and ongoing maintenance, digitization acts as a catalyst for positive change in projects.The article examines how building information modeling technologies fit within existing systems and project management actors commonly used in engineering practice and improve them. Issues related to data sharing and collaboration between interdisciplinary team members (designers, contractors, developers, suppliers, engineering firms, etc.) are addressed, demonstrating how building information modeling can be integrated into a variety of engineering processes.By offering a synthesis of methodological approaches, practical ideas, and overarching principles, the paper provides academics and construction professionals with a framework for implementing VIM, contributing to a paradigm shift toward more advanced, sustainable, and effective engineering practices.